Pengembangan Wilayah Berdasarkan Komoditas Unggulan di Kecamatan Petang, Kabupaten Badung, Provinsi Bali - PRATAMA, I PUTU SURYA; ANTARA, MADE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Regional economic growth is essentially a series of businesses and policies aimed at improving economic relations from the primary sector to the secondary and tertiary sectors. Economic development is a policy focused on improving people's living standards, expanding employment, declaring revenue sharing and improving regional relationships among regions. The balance of development in North Badung and South Badung is often a discourse. The synergy of the tourism and agriculture sectors is the answer to making this happen. This study aimed to identify superior and non-superior commodities as well as formulate a strategy of developing superior commodities in Petang District. The data used were secondary data in the form of time series data or agricultural production data of Badung Regency and Petang District in 2011-2015. The data were collected by document study and in-depth interviews, analyzed by Location Quotient (LQ) and SWOT analysis method. The result of the analysis shows that food commodities belonging to the main commodities are corn, peanut, sweet potato, cassava and asparagus while the rice commodity is included in non-commodity commodity. Plantation commodities included in the main commodities are coffee, cloves and vanilla, while coconut and cocoa are included in non-commodity commodities. Strategic development of superior commodities that need to be taken is to explore the potential of natural resources and improve the quality of human resources for the development of superior commodities in Petang District.